Effects of Seated Postural Stability and Trunk and Upper Extremity Strength on Performance during Manual Wheelchair Propulsion Tests in Individuals with Spinal Cord Injury: An Exploratory Study. (18th August 2016) - Gagnon, Dany H.; Roy, Audrey; Gabison, Sharon; Duclos, Cyril; Verrier, Molly C.; Nadeau, Sylvie
Abstract : Objectives. To quantify the association between performance-based manual wheelchair propulsion tests (20 m propulsion test, slalom test, and 6 min propulsion test), trunk and upper extremity (U/E) strength, and seated reaching capability and to establish which ones of these variables best predict performance at these tests. Methods. 15 individuals with a spinal cord injury (SCI) performed the three wheelchair propulsion tests prior to discharge from inpatient SCI rehabilitation. Trunk and U/E strength and seated reaching capability with unilateral hand support were also measured. Bivariate correlation and multiple linear regression analyses allowed determining the best determinants and predictors, respectively. Results. The performance at the three tests was moderately or strongly correlated with anterior and lateral flexion trunk strength, anterior seated reaching distance, and the shoulder, elbow, and handgrip strength measures. Shoulder adductor strength-weakest side explained 53% of the variance on the 20-meter propulsion test-maximum velocity. Shoulder adductor strength-strongest side and forward seated reaching distance explained 71% of the variance on the slalom test. Handgrip strength explained 52% of the variance on the 6-minute propulsion test. Conclusion. Performance at the manual wheelchair propulsion tests is explained by a combination of factors that should be considered in rehabilitation.